معدلات وعوامل انتشار الاستخدام غير الطبي للعقاقير الصيدلانية: الأدوية النفسية - الجعفراوي، إيناس إبراهيم; رمضان، هالة; محي الدين، ريهام; خليل، نجوى حسين; عبدالجواد، ليلى أحمد (المركز القومي للبحوث الاجتماعية والجنائية, 2021)
تعرض الدراسة الراهنة لمعدلات انتشار الاستخدام غير الطبي للعقاقير الصيدلانية في مصر والعوامل المؤثرة، مثل الخصائص الديموجرافية لمستخدميها وسياق تناولها، وقد تم التطبيق على عينة مكونة من (25) ألف أسرة، بمدى عمري من (12- 60) عاما من مختلف المحافظات، وطبقت استمارة استبار مكونة من (107) أسئلة. ونعرض في هذه الدراسة للنتائج المتعلقة بنسبة انتشار استخدام العقاقير الصيدلانية دون الرجوع للطبيب، والمتعلقة بمتغيرات النوع والعمر، والحالة الاجتماعية، والتعليم والمهنة، وكذلك المتغيرات المرتبطة بخبرات التعاطي، ونوع العقاقير التي يتم تعاطيها وكيفية حصولهم عليها وتكلفتها والدوافع وراء استخدامها. The current study presents the prevalence rate of non-medical use of pharmaceutical drugs in Egypt and its associated factors, such as the demographic characteristics of its abusers, its context, and the associated ideas and beliefs. It was applied on a sample of 25,000 families between 12 and 60 years old from various governorates of Egypt. An interview questionnaire consisting of 107 questions was applied. In this study we present the results related to the prevalence of non-medical use of pharmaceutical drugs without referring to the doctor, which is related to the variables of gender, age, marital status, education and profession, as well as variables related to the abuse experience, the type of the drugs abused, the way of obtaining them, their cost and the reasons of using them.
Keywords: الدراسات الطبية -- العقاقير الطبية -- الأدوية النفسية -- إدمان المخدرات